Analysis of Multifactor that Influences Grabfood Consumer Behaviour During the Covid-19 Pandemic - Rois Arifin; Dita Roosemella Paramadina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this research is to analyze the significance of the effect of e-service quality, price and e - promotion on e-customer satisfaction during Covid-19 pandemic in Malang City. The research method used is quantitative research methods, sampling techniques data by distributing questionnaires to 150 respondents using purposive sampling technique. Methods of data analysis using Validity and Reliability tests, Multiple Linear Regression, Statistical F Test and Statistical Test t. The results of the study with the F statistical test obtained that e-service quality, price and e - promotion simultaneously have a significant effect on e-customer satisfaction at Grabfood During pandemic. Meanwhile, through the t statistical test, it was obtained that e-service quality, price and e - promotion partially had a significant effect on e-customer satisfaction at Grabfood During pandemic.